2021
DOI: 10.1007/s00464-020-08249-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of COVID-19 and the bariatric surgery population: a single center experience

Abstract: Background While many cases of the coronavirus disease 2019 are mild, patients with underlying medical conditions such as hypertension (HTN), diabetes mellitus (DM), older age, and morbid obesity are at higher risk of hospitalization and death. These conditions are characteristic of patients eligible for bariatric surgery, many of whom underwent weight loss procedures in the months prior to cessation of elective surgery in March 2020. The effects of the virus on these high-risk patients who had increased heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…No mortality was reported, and no need for an intermediate or ICU bed was required. These results are in accordance with previous studies that report overall complications rates between 1 and 6.8%, major complications between 1 and 2.4%, and mortality rates between 0 and 0.5% [ 13 15 , 20 ]. Combined, these results are in line with pre-pandemic reported outcomes, indicating the safety of bariatric surgery with morbidity and mortality rates of 5% or less and 0.1%, respectively [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…No mortality was reported, and no need for an intermediate or ICU bed was required. These results are in accordance with previous studies that report overall complications rates between 1 and 6.8%, major complications between 1 and 2.4%, and mortality rates between 0 and 0.5% [ 13 15 , 20 ]. Combined, these results are in line with pre-pandemic reported outcomes, indicating the safety of bariatric surgery with morbidity and mortality rates of 5% or less and 0.1%, respectively [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Perioperative COVID-19 infection has negatively impacted the safety of patients undergoing surgery, increasing complications and mortality rates [ 1 , 4 ]. Currently, only a few studies have reported data on the risk of perioperative COVID-19 infection and safety outcomes in patients undergoing bariatric surgery during the ongoing pandemic [ 13 15 , 20 ]. One study reported 87 consecutive patients who underwent SG during the opening phase between the first and second COVID-19 waves [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited data studying the effects of the pandemic in patients with complex multifactorial diseases such as obesity. We previously discussed the short-term exposure risk of an active bariatric cohort at the height of the COVID-19 pandemic [8]. However, the long-term effects of undergoing bariatric surgery at the time of a worldwide pandemic and its impact on the success of participation in the bariatric surgery program, from preparation for surgery through postoperative follow-up, are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the COVID-19 pandemic on preoperative weight management, the infection risk, and perioperative outcomes of several bariatric cohorts have been discussed [8]. However, longer term data on the impact of the COVID-19 pandemic on weight loss after surgery is needed.…”
Section: Key Pointsmentioning
confidence: 99%